(untitled) (Bioresearch Communications, 2025)
The main objective of the present study was to adapt and validate the Class-Related Emotions Questionnaire in Bangla. Because class-related emotions significantly impact academic achievement, the study aimed to develop a psychometrically valid tool for evaluating class-related emotions in Bangladeshi cultural settings. A six-step adaptation process was followed to ensure the questionnaire’s language and cultural suitability, including forward translation, expert review, reverse translation, and pretesting. Using a purposive sampling technique, data were collected from 349 participants at four public universities. The confirmatory factor analysis indicated that the Bangla version of the Class-Related Emotions Questionnaire has excellent internal consistency (Cronbach’s alpha = 0.927), test-retest reliability (r = 0.932), and construct validity. Furthermore, a significant positive correlation was found among its eight subscales. This result indicated that the Bangla version of the Class-Related Emotions Questionnaire was a reliable and valid tool for assessing the impact of emotions on academic engagement and success in the Bangladeshi educational context. Bioresearch Commu. 11(2): 1826-1834, 2025 (July)